Problem-based learning and the promotion of problem solving: choices for physical therapy curricula. - Jefferson JR (Journal of Physical Therapy Education (American Physical Therapy Association, Education Section))
Proponents of problem-based learning (PBL) have stated that its approach helps students develop effective and efficient problem-solving skills. The purpose of this article is threefold: (1) to explain the differences between PBL and problem solving, (2) to review the current literature on PBL for evidence that PBL promotes the development of problem-solving skills, and (3) to suggest alternative strategies to promote problem solving in physical therapy curricula. Problem-based learning uses problem solving but is much more than just problem solving. Problem-based learning is a curriculum-wide approach, it is a problem-first approach, it is integrative across disciplines, and it is metacognitive in its form of evaluation. The literature suggests that repeated exposure to PBL sessions does not improve students' problem-solving skills. Recent evidence suggests that clinical expertise is related to the extent of a person's knowledge base, and in that respect PBL, with it's de-emphasis on content, may actually be deterring the problemsolving process. The use of PBL should be selective, and highly structured, if our instructional goal is the promotion of clinical problem-solving skills.